Maritime Limit Conflict, Illegal Fishing and Enformance of Effort in Natuna Sea Region between Indonesia and China - Gayuh Nugroho Dwi Putranto; Muhammad Zid; Mieke Miarsyah (JURNAL PERIKANAN DAN KELAUTAN, 2019)
Indonesia tries to protect sea areas to avoid illegal fishing cases and maritime boundary disputes. Illegal fishing that occurred in Natuna resulted in decreased income from the fishery side due to the existence of illegal fishing practices. Various attempts have been made by the Indonesian government to deal with illegal fishing by foreign fishermen and local fishermen. The case of illegal fishing that occurred at the end of 2019 was carried out by the Chinese state in Natuna waters which had triggered tension between Indonesia and China, which was triggered by different perceptions related to maritime boundaries where China used the nine-dash line concept that was not by UNCLOS recognized by the UN. This study aims to explain the nine-dash line concept that underlies unilateral claims to China, and the concept of UNCLOS which underlies ownership of the Natuna waters by Indonesia and efforts to enforce illegal fishing in the Natuna Islands. The study was conducted descriptively based on secondary data based on Indonesia's sovereign rights over the Natuna Islands. The results show that China's claim to Natuna based on the nine-dash lines does not form the basis of applicable international law